Taxonomic notes on poorly known species of potter wasps (Vespidae: Eumeninae: Zethini) from India. (3rd July 2019) - Pannure, Arati; Belavadi, Vasuki V.; Carpenter, James M.
ABSTRACT: Potter wasps belonging to the tribe Zethini are reviewed from India. A new synonym, Discoelius nigerrimus Nguyen, syn. nov .  =  Discoelius turneri, is proposed. Zethus ceylonicus de Saussure, is re-described and the male recorded for the first time. A key to species of the tribe Zethini from India is included.